A Critical Literary Review on Role of Rakthamokshana and Arka Taila in Vicharchika - Yadav, Shipra; Kapoor, Ritu (International Research Journal of Ayurveda & Yoga, 2023)
Vicharchika is a type of Kshudra Kushtha often encountered by Ayurvedic Dermatologists characterized with symptoms, namely, kandu, srava, pidika, and shyava varna. Based on clinical manifestations, vicharchika is frequently linked to eczema. Modern dermatology compares the clinical appearance of Vicharchika to eczema. The most typical kind of dermatitis is eczema. It is believed that the pathogenesis is influenced by both genetic and environmental factors. Despite being present in adults, eczema is more frequently encountered in youngsters. Dry, itchy skin that has poorly defined regions of erythema and scale is a hallmark of eczema, also known as atopic dermatitis. Eczema can be vesicular and ooze when it is acute, but it can also become hyperpigmented and lichenified (thickened) when it is chronic. Scratches or excoriations are commonly observed. Eczema is a symptom that Ayurveda treats, as it holds that all doshas must be in balance for health to exist. However, it does not address the basis of the problem. Recurrence is thus highly common. By balancing the Dosha and Dhatus and purging vitiated Dosha, Ayurveda treats the underlying cause of eczema.